2016
DOI: 10.1007/s00586-016-4840-6
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a dynamic surgical guidance probe for screw insertion in the cervical spine: a cadaveric study

Abstract: The dynamic surgical guidance probe is a safe tool to assist the surgeon with screw placement in the cervical spine. Additionally, the DSG potentially avoids the cumulative risks associated with fluoroscopy and provides real-time feedback to the surgeon allowing correction at the time of breach. Level of evidence Level IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Koller et al 17 . and Dixon et al 28 . did preliminary researches on cadavers on cervical and thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koller et al 17 . and Dixon et al 28 . did preliminary researches on cadavers on cervical and thoracic spine.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, studies carried out to prove the accuracy in different conditions. Koller et al 17 and Dixon et al 28 did preliminary researches on cadavers on cervical and thoracic spine. Williams et al 29 also did a cadaver study and found that the sensitivity to detecting cortical breach was 97% in pedicle drillings and 84% in vertebral body drillings, respectively.…”
Section: Safety and Effectiveness Of The Modified Ecd Withmentioning
confidence: 99%
“…The instrument was found to be a safe tool that assists the surgeon with screw placement in the cervical spine. Additionally, it potentially avoids the cumulative risks associated with fluoroscopy (radiation exposure) and provides real‐time feedback to the surgeon, thus allowing correction at the time of breach …”
Section: Discussionmentioning
confidence: 99%
“…This device uses audio alerts and light-emitting diode warning signals to guide surgeons. According to a limited number of papers [16,[20][21][22][23][24][25][26][27][28], the usefulness of ECD for pedicle proving has been reported during posterior fusion surgery for scoliosis, degenerative disease, and tumors. However, no evidence exists regarding its efficacy even for syndromic and neuromuscular scoliosis in which pedicle screw placement is extremely difficult.…”
Section: Introductionmentioning
confidence: 99%